2016
DOI: 10.18869/modares.jcp.5.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 16SrII group phytoplasmas associated with alfalfa (Medicago sativa) witches’ broom disease in diverse areas of Iran

Abstract: Alfalfa witches' broom (AWB) is one of the most important alfalfa diseases in Iran. To characterize 16SrII group phytoplasmas associated with this disease, symptomatic and asymptomatic plants were collected during 2013-2015 and subjected to direct and nested polymerase chain reaction (PCR) using P1/P7, R16mF2/R16mR2 and R16F2n/R16R2. PCR amplicons of ~1.8, ~1.4 and ~1.25 kb respectively, were obtained only from all symptomatic plants. Restriction fragment length polymorphism (RFLP) analysis of R16F2n/R2 amplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, detailed studies have shown that WBDL‐Ir phytoplasma (“ Ca . P. aurantifolia,” 16SrII‐B) and AlfWB‐Y phytoplasma (16SrII‐C) have different natural and experimental host ranges and are vectored by different insects (Esmailzadeh Hosseini, Khodakaramian, Salehi, & Bertaccini, ; Salehi, Izadpanah, & Ebrahim Nesbat, ; Salehi, Izadpanah, Siampour, Bagheri, & Faghihi, ). Phylogenetic analysis of this study also identified WBDL phytoplasma on a sub‐lineage distinct from phytoplasmas of 16SrII‐C.…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed studies have shown that WBDL‐Ir phytoplasma (“ Ca . P. aurantifolia,” 16SrII‐B) and AlfWB‐Y phytoplasma (16SrII‐C) have different natural and experimental host ranges and are vectored by different insects (Esmailzadeh Hosseini, Khodakaramian, Salehi, & Bertaccini, ; Salehi, Izadpanah, & Ebrahim Nesbat, ; Salehi, Izadpanah, Siampour, Bagheri, & Faghihi, ). Phylogenetic analysis of this study also identified WBDL phytoplasma on a sub‐lineage distinct from phytoplasmas of 16SrII‐C.…”
Section: Discussionmentioning
confidence: 99%
“…widespread and economically important disease (Esmailzadeh Hosseini et al, 2016), transmitted by the leafhopper Orosious albicinctus (Salehi et al, 1995). Thus, alfalfa and O. albicinctus could be involved in the transmission of 'Ca.…”
mentioning
confidence: 99%
“…The phytoplasmas found in weeds around the world mostly belong to the 16SrI, 16SrII, 16SrXI, 16SrXII, and 16SrXIV groups, but some members of the 16SrIII, 16SrIV, 16SrV, 16SrVI, 16SrVII, 16SrIX, 16SrX, and 16SrXXIX groups have also been identified (Duduk et al 2018). Also, studies have shown that while A. retroflexus weed is infested with the 16SrI group, and 16SrV-B and 16SrXII-A subgroups (Credi et al 2006, Wu et al 2010, Yang et al 2011 (Credi et al 2006, Esmailzadeh Hosseini et al 2016a, 2016b. Infections by 16SrIX-C 'withes`s broom' , 16SrI-(B/AJ), and 16SrXII-A phytoplasma subgroups have been reported in wild plants S. arvensis, C. maculatum, and D. carota wild, respectively (Casati et al 2016, Fernández et al 2020, Sertkaya 2014.…”
Section: Discussionmentioning
confidence: 99%